Structured light for optical communication - Al-Amri, Mohammad D.; Andrews, David L., 1952-; Babiker, Mohamed (Nanophotonics series., 2021)
Structured Light for Optical Communication highlights principles and applications in the rapidly evolving field of structured light in wide-ranging contexts, from classical forms of communication to new frontiers of quantum communication. Besides the basic principles and applications, the book covers the background of structured light in its most common forms, as well as state-of-the-art developments. Structured light has been hailed as affording outstanding prospects for the realization of high bandwidth communication, enhanced tools for more highly secure cryptography, and exciting opportunities for providing a reliable platform for quantum computing. This book is a valuable resource for graduate students and other active researchers, as well as others who may be interested in learning about this cutting-edge research field.